Innovationsräume - Lang, Thilo (Dialektik des Globalen. Kernbegriffe, 2019)
This volume examines the relationships between innovation and space, illustrating a range of phenomena subsumed in the concept of innovation spaces. It presents new conceptualizations of innovation as a dynamic, territorially unfettered process, and describes alternative forms of proximity and distance in innovation processes, issues that have been largely neglected to date in the discourse on the relationship between innovation and space.